COMBINING STUDENT-BASED LEARNING ACTIVITIES WITH TEACHER’S ENCOURAGEMENTS TO FOSTER LEARNER AUTONOMY IN ELT - Sudarsono, Sudarsono; Lestari, Lies Amin (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2016)
Teacher’s domination and authority used to prevail the traditional language teaching is now left and replaced by more acceptable concept of teaching. This concept emphasizes on developing the sense of learners’ responsibility, independence, or autonomy, for better learning outcome. Autonomous language learners are those assumed to have greater responsibility on their own learning for their own needs. A series of guided practice through a step-by-step manner is needed in order that students can be possibly trained to be autonomous, independent learners. This paper discusses learning activities created and designed by the students combined with teacher’s encouragements to foster learner autonomy. Some theories and previous studies on learner autonomy are analyzed to support the discussion. It is believed that the combination between the two important aspects in autonomous language learning will strengthen the efforts of promoting learner autonomy in ELT. Keywords: English language teaching, learner autonomy, autonomous learning, learning activities, teacher’s encouragement